2022
DOI: 10.1177/14791641221137736
|View full text |Cite
|
Sign up to set email alerts
|

Glycaemic variability and risk of adverse cardiovascular events in acute coronary syndrome

Abstract: Objective The relationship between different glycaemic variability (GV) indexes and adverse cardiovascular outcomes is not well understood. This study aims to determine whether GV is related to the occurrence of adverse cardiovascular events in patients with acute coronary syndrome (ACS). Methods PubMed, EMBASE, and Web of Science were comprehensively searched from the establishment of databases to 29 June 2022. The relationship between two important GV indexes, including the mean amplitude of glycemic excursi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…More and more recent studies have focused on GV and its association with the prognosis of coronary artery disease, and a meta-analysis indicated that increased GV may be associated with poor prognosis in coronary artery disease patients regardless of DM status [ 17 ]. Similarly, another meta-analysis suggested that increased GV is correlated with poorer prognosis in acute coronary syndrome patients [ 18 ]. Specifically for acute myocardial infarction, Zhang et al first demonstrated that GV serves as an independent predictor for composite 30-day MACEs in DM patients with STEMI undergoing primary PCI [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…More and more recent studies have focused on GV and its association with the prognosis of coronary artery disease, and a meta-analysis indicated that increased GV may be associated with poor prognosis in coronary artery disease patients regardless of DM status [ 17 ]. Similarly, another meta-analysis suggested that increased GV is correlated with poorer prognosis in acute coronary syndrome patients [ 18 ]. Specifically for acute myocardial infarction, Zhang et al first demonstrated that GV serves as an independent predictor for composite 30-day MACEs in DM patients with STEMI undergoing primary PCI [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Variability in glucose levels was determined based on the SD (mg/dL) and CV of all the available blood glucose measurements within 1 year of surgery. To calculate the CV, the following formula was used: CV = (SD/mean value) × 100% ( 19 ). In the absence of any information regarding the timing of the glucose testing with respect to eating, glucose scores were considered to represent random, non-fasting assessments.…”
Section: Methodsmentioning
confidence: 99%
“…[42][43][44][45] Several studies in critically ill and non-critically ill hospitalized patients have shown the independent association between high GV and poor clinical outcomes. [35][36][37]42,43,45,46,47 Although studies assessing GV have usually included all value points during hospital stay, evaluation of daily data on hospitalized patients may provide sufficient information to make therapeutic changes when needed. Though multiple metrics have been suggested to measure GV, CV, and SD are the most commonly reported.…”
Section: Hospital Glycemic Variabilitymentioning
confidence: 99%